The electroanalytical detection and determination of copper in heavily passivating media: ultrasonically enhanced solvent extraction by N-benzoyl-N-phenyl-hydroxylamine in ethyl acetate coupled with electrochemical detection by sono-square wave stripping voltammetry analysis. - Hardcastle, J; Compton, R (2001)
N-benzoyl-N-phenyl-hydroxylamine dissolved in ethyl acetate was employed as a ligand for the solvent extraction of copper. Ultrasonic emulsification was shown to be effective both in the extraction of copper from an aqueous phase into ethyl acetate and its recovery or "back extraction" into a fresh clean aqueous solution. Experimental determination of thermodynamic parameters governing the extraction process via UV/visible spectroscopy is reported. This permitted theoretical predictions for the amount of copper transferred into the final aqueous solution to be fitted to experimental data. Quantitative analysis of copper removed via double sono-extraction from an aqueous medium hostile to voltammetric analysis proceeded via sono-square wave anodic stripping voltammetry analysis (sono-SWASV). This resulted in very high sensitivity in the relatively clean medium. The technique was then applied to the analysis of copper in the soft drink 'Ribena Light'. In the absence of sample preparation by solvent extraction sono-SWASV yields a measurable peak current for copper. However it is irreproducible and erratic due to passivating effects, possibly attributed to the sugars, natural flavourings and colourings present. Following sono-solvent extraction, the overall copper concentration could be obtained with a detection limit of 2 microg L(-1). Biphasic sono-extraction synergistically coupled with the recognized technique sono-SWASV presents an attractive technique for copper analysis in electrode passivating media. The technique necessarily removes contaminants present in the test solution since these will prefer to remain in the initial aqueous phase, or will transfer to the organic phase but are unlikely to be doubly transferred into the 'clean' final aqueous phase.